2012
DOI: 10.1039/c2an35172b
|View full text |Cite
|
Sign up to set email alerts
|

Facile, rapid and efficient biofabrication of gold nanoparticles decorated with functional proteins

Abstract: We report a one-pot biological approach to fabricate gold nanoparticle (AuNP)-ZZ domain conjugates using peptide-functionalized proteins that can simultaneously direct both biomineralization and surface modification of AuNPs. In addition, immuno-AuNPs are readily prepared through the specific binding of antibodies to the ZZ domain on the AuNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
4
10
0
Order By: Relevance
“…AuNPs were synthesized in the presence of rBSA or BSA according to the method described for AuNP synthesis using the A3 peptide 15 . A solution consisting of AuCl4 -(0.25 mM), rBSA or BSA (2 μM), and HEPES buffer (10 mM, pH 8) was incubated overnight at 27°C.…”
Section: Preparation Of Rbsa-functionalized Aunpmentioning
confidence: 99%
See 1 more Smart Citation
“…AuNPs were synthesized in the presence of rBSA or BSA according to the method described for AuNP synthesis using the A3 peptide 15 . A solution consisting of AuCl4 -(0.25 mM), rBSA or BSA (2 μM), and HEPES buffer (10 mM, pH 8) was incubated overnight at 27°C.…”
Section: Preparation Of Rbsa-functionalized Aunpmentioning
confidence: 99%
“…To overcome the limitations of the above-mentioned methods, the synthesis of AuNP by using peptides and proteins has been reported, wherein the reducing ability of amino acid residues such as cysteine and tyrosine is utilized 12,13 . For example, AuNPs with a size of 10-15 nm were synthesized by an A3 peptide (AYSSGAPPMPPF) using tyrosine residues as the reducing agents 14,15 . Slocik et al also reported AuNP synthesis using YYY peptide 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The pH of the aqueous solutions was adjusted by the addition of either HNO 3 or NaOH to a 10 mM or 100 mM 2-morpholinoethanesulfonic acid (MES) buffer. In the extraction tests with metal chlorides (Ru(III), Rh(III), Pd(II), Hf(IV), Os(IV), Ir(III), Pt(IV), and Au(III)), the pH was adjusted by the addition of HCl to a 50 mM sodium acetate buffer at a constant ionic strength of 0.1 M NaCl because the MES buffer can easily reduce Au(III) to Au(0) [23][24][25]. In the extraction of K(I), Hg(II), and Ag(I), the contamination of aqueous solutions by potassium ions and chloride ions from the pH electrode was prevented.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…(Caution: do not use the MES buffer for Au(III) extraction because MES can easily reduce Au(III) to Au(0). [19][20][21] ) In extraction tests of rare-earth metal ions, the pH was adjusted by dilution with HNO3 without a buffer. For Ag(I) and Hg(II) extraction, the contamination of aqueous solutions by chloride ions from the pH electrode was prevented.…”
Section: Extraction Proceduresmentioning
confidence: 99%